2022
DOI: 10.1021/acscatal.2c04275
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Reconstruction of Cu–N Coordinated MOFs to Generate Dispersive Cu/Cu2O Nanoclusters for Selective Electroreduction of CO2to C2H4

Abstract: Electrochemical reduction of CO2 to obtain high-value-added feedstocks is a promising strategy to alleviate the energy crisis. Cu-based catalysts generate multi-carbon products with high activity in the CO2 reduction reaction (CO2RR), although great challenges remain in the selectivity and stability of Cu-based catalysts. Here, highly active Cu/Cu2O nanoclusters were produced via in situ electrochemical reconstruction using Cu–N coordinated MOFs as precursors for the highly selective C2H4 synthesis, showing a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(43 citation statements)
references
References 91 publications
0
32
0
Order By: Relevance
“…This distinct observation underscores the good maintenance of Cu + within Ce-Cu 2 O. In situ Raman spectroscopy was further employed to monitor the oxidation of copper in CO 2 -flowed 0.1 M KHCO 3 electrolyte under a potential of −1.3 V, with corresponding devices shown in Figure S17 . As depicted in Figure E, for both Ce-Cu 2 O and pure Cu 2 O, Raman signals at 213, 419, 524, and 624 cm –1 , which are ascribed to the 2 Γ – 12 , 4 Γ – 12 , Γ + 25 , and Γ – 12 + Γ + 25 phonon modes, respectively, were observed. , Notably, the Raman phonon modes (e.g., the 2 Γ – 12 mode) after 120 min were well-retained for Ce-Cu 2 O (Figure E) under genuine operando conditions.…”
Section: Resultsmentioning
confidence: 99%
“…This distinct observation underscores the good maintenance of Cu + within Ce-Cu 2 O. In situ Raman spectroscopy was further employed to monitor the oxidation of copper in CO 2 -flowed 0.1 M KHCO 3 electrolyte under a potential of −1.3 V, with corresponding devices shown in Figure S17 . As depicted in Figure E, for both Ce-Cu 2 O and pure Cu 2 O, Raman signals at 213, 419, 524, and 624 cm –1 , which are ascribed to the 2 Γ – 12 , 4 Γ – 12 , Γ + 25 , and Γ – 12 + Γ + 25 phonon modes, respectively, were observed. , Notably, the Raman phonon modes (e.g., the 2 Γ – 12 mode) after 120 min were well-retained for Ce-Cu 2 O (Figure E) under genuine operando conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were used to characterize the morphology of the as-prepared Por(Co)-Vg-COF. 63 The SEM images showed that the Por(Co)-Vg-COF was composed of spherical particles (Fig. S6, ESI †).…”
Section: Resultsmentioning
confidence: 99%
“…26 To meet the requirements for commercial applications, the excellent CO 2 RR performance of Por(Co)-Vg-COF in neutral electrolyte encouraged us to further improve its electrocatalytic performance with a large current density using a gas-diffusion electrode (GDE) in acidic media, which could offer an avenue to reduce carbonate formation and eliminate CO 2 crossover, and this was the first COF catalyst reported for CO 2 RR in acidic/ alkaline conditions. 37,[63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78] The CO 2 RR of Por(Co)-Vg-COF in 0.06 M H 2 SO 4 with a 0.5 M K 2 SO 4 additive was first tested. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One point to note in particular is that the genuine active site of the MOF should be meticulously judged when pristine MOFs are subjected to electrocatalytic CO 2 RR, as the MOF structure may evolve under working time. [19][20] For example, Yi et al constructed a porous conductive copper-based metal-organic framework (CuHHTP) for the electrocatalytic CO 2 RR process. [21] As a result of Operando IR spectroscopy and DFT calculations, the in-situ generated Cu 2 O(111) quantum dot is the true active site for electrochemical reduction to CH 4 and is not an independently distributed Cu metal site in CuHHTP.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, some MOFs have CO 2 adsorption capacity, which is beneficial to increase the local CO 2 concentration of MOFs during CO 2 RR. One point to note in particular is that the genuine active site of the MOF should be meticulously judged when pristine MOFs are subjected to electrocatalytic CO 2 RR, as the MOF structure may evolve under working time [19–20] . For example, Yi et al.…”
Section: Introductionmentioning
confidence: 99%